Comparison of the cachexia index based on hand-grip strength (H-CXI) with the original CXI for the prediction of cancer cachexia and prognosis in patients who underwent radical colectomy for colorectal cancer - Yan, Xia-Lin; Wu, Lian-Ming; Tang, Xiu-Bo; Li, Zong-Ze; Zhang, Zhao; Jiang, Hao-Jie; Chen, Zhang-Tao; Chen, Ding-Hao; Li, Jiang-Yuan; Shen, Xian; Huang, Dong-Dong (Frontiers in Nutrition, 2024)
Background &Aims: Cachexia index (CXI) was a novel biomarker for estimating cancer cachexia. Cachexia index based on hand-grip strength (H-CXI) was developed recently as a simple proxy for CXI. The present study aims to compare H-CXI and CXI for the prediction of cancer cachexia and postoperative outcomes in patients underwent radical colectomy for colorectal cancer. Methods: Patients who underwent radical operations for colorectal cancer were included in this study. Cancer cachexia was diagnosed according to the international consensus by Fearon et al. Cachexia index (CXI) was calculated as [skeletal muscle index (SMI) × serum albumin / neutrophil to lymphocyte ratio (NLR)]. H-CXI was calculated as [hand-grip strength (HGS) / height 2 × serum albumin / NLR]. SMI was measured based on the preoperative CT images at the third lumbar vertebra (L3) level. HGS was measured before surgery. Results: From July 2014 to May 2021, a total of 1411 patients were included in the present study, in which 361 (25.6%) were identified as cancer cachexia. Patients with cachexia had lower CXI (P <0.001) and lower H-CXI (P <0.001) compared with those without cachexia. Low CXI but not low H-CXI independently predicted cancer cachexia in the multivariate analysis (OR 1.448, P = 0.024). Both low CXI (HR 1.476, P <0.001 for OS; HR 1.611, P <0.001 for DFS) and low H-CXI (HR 1.369, P = 0.007 for OS; HR 1.642, P <0.001 for DFS) were independent predictors for overall survival (OS) and disease-free survival (DFS) after adjusting for the same covariates. Low H-CXI but not low CXI was an independent risk factor for postoperative complications (OR 1.337, P = 0.044). No significant association was found between cancer cachexia and postoperative complications. Conclusion: CXI and H-CXI had better prognostic value than cancer cachexia for the prediction of postoperative outcomes in patients underwent radical colectomy for colorectal cancer. H-CXI was a superior index over CXI in predicting short-term clinical outcomes. Whereas CXI had closer correlation with Fearon's criteria of cancer cachexia. Ideal tools for assessment of cancer cachexia should incorporating not only weight loss, but also muscle mass, physical function, and inflammatory state.